Pengaruh Return On Asset (ROA), Earning Per Share (EPS), dan Ukuran Perusahaan, terhadap Nilai Perusahaan - Fitriya Nur Indah Sari; Wulandari Agustiningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Various companies have experienced significant developments that have led to the emergence of business competition in Indonesia, to attract investors to invest in these companies, one of the most important factors to consider is the value of the company. This study aims to determine the effect of return on assets, earnings per share, and firm size on firm value in food and beverage sub-sector companies simultaneously and partially. The dependent variable used in this study is firm value. The sample data was obtained through financial statements listed on the Indonesia Stock Exchange. This study uses quantitative methods, the analytical technique used is descriptive statistics, while hypothesis testing uses multiple linear regression analysis. The determination of the sample was carried out using the purposive sampling method in the food and beverage sub-sector companies for the 2016-2020 period. The results of this study indicate that simultaneously return on assets, earnings per share, and firm size have an effect on firm value. Partially, return on assets, earnings per share have a positive effect on firm value, while firm size has no effect on firm value.